The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/08901171211068401
|View full text |Cite
|
Sign up to set email alerts
|

From Compliance to Adherence in Diabetes Self-Care: Examining the Role of Patient’s Potential for Mindful Non-Adherence and Physician-Patient Communication

Abstract: Purpose: To examine the roles of patient mindful non-adherence and physician-patient communication as important factors that facilitate an understanding of the relationship between compliance and adherence in diabetes management. Design: A cross-sectional survey Setting: Online data collection Subjects: 365 respondents at least 18 years of age and currently in treatment for diabetes Measures: We measured patients’ compliance, adherence, mindfulness, and perceptions about physician-patient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Сложившееся к началу текущего столетия терминологическое многообразие, описывающее отношение пациента к исполнению медицинских предписаний, впоследствии продолжало расширяться, как за счет введения в оборот синонимов, так и за счет придания определениям смысловых www.jscientia.org нюансов. С другой стороны, во многих источниках термины комплаенс, приверженность и близкие к ним стали использоваться как взаимозаменяемые синонимы [1,[9][10][11].…”
Section: терминологияunclassified
“…Сложившееся к началу текущего столетия терминологическое многообразие, описывающее отношение пациента к исполнению медицинских предписаний, впоследствии продолжало расширяться, как за счет введения в оборот синонимов, так и за счет придания определениям смысловых www.jscientia.org нюансов. С другой стороны, во многих источниках термины комплаенс, приверженность и близкие к ним стали использоваться как взаимозаменяемые синонимы [1,[9][10][11].…”
Section: терминологияunclassified
“…Soyoon & Ekaterina (19) argue that when patients effectively engage in self-care behaviors, they can better connect with their bodies. Mindfulness brings awareness to the present moment and bodily sensations, including both pleasant and unpleasant feelings, through meditation practices or physical awareness.…”
Section: Introductionmentioning
confidence: 99%
“…In diabetes care, goal setting is generally conducted by physicians who collaborate with patients to set short-term and specific goals[ 58 ], such as diet-related goals[ 59 ], and feedback is also provided by physicians. Patients and doctors are usually involved in established partnerships and collaborations[ 60 ]. Evidence has shown that a patient-empowerment approach using collaborative goal setting improves A1C[ 61 ].…”
Section: Introductionmentioning
confidence: 99%